Exportación de velas con partida arancelaria 34060000 hacia los Estados Unidos - Garavito Mariño, Pilar Elizabeth (Universidad Antonio Nariño, 2022)
The company PielArt, has a journey in the market for years, this company arose with the initiative to commercialize and / or develop products such as: carved candle, handmade candle, scented candle, candle, candles and candle holder designs, in different sizes, prices, aromas, and presentations. What used to be an arrangement has gradually been strengthened.